2019
DOI: 10.1097/md.0000000000015492
|View full text |Cite
|
Sign up to set email alerts
|

Decision analysis about the cost-effectiveness of different in vitro fertilization-embryo transfer protocol under considering governments, hospitals, and patient

Abstract: Objective: The aim of this study was to explore the benefits of in vitro fertilization (IVF) for patients and hospitals under different protocols and if IVF treatment should be incorporated into health care. Perspective: The government should consider including IVF treatment in health insurance. Hospitals and patients could obtain the best benefit by following the hospital's recommended protocol. Setting: This retrospective study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Our study showed that one full-dose depot of long-acting GnRH-a per COH cycle would be more suitable and convenient for infertile couples than GnRH antagonist and short-acting GnRH-a injections during the COVID-19 pandemic because there are fewer possible incidences of potential exposure ( Ren et al, 2014 ; Li F. et al, 2020 ). Some studies previously observed that a pituitary downregulated full-dose may require a higher dose of gonadotropins for ovarian stimulation ( Pan et al, 2019 ; Xu et al, 2020 ); however, our study showed that the total dosage of Gns used in our study was not statistically different among the treatment groups, which means a full dose of gonadotropins or prolonged pituitary downregulation would not drastically increase the economic burden for Infertile couples.…”
Section: Discussioncontrasting
confidence: 74%
“…Our study showed that one full-dose depot of long-acting GnRH-a per COH cycle would be more suitable and convenient for infertile couples than GnRH antagonist and short-acting GnRH-a injections during the COVID-19 pandemic because there are fewer possible incidences of potential exposure ( Ren et al, 2014 ; Li F. et al, 2020 ). Some studies previously observed that a pituitary downregulated full-dose may require a higher dose of gonadotropins for ovarian stimulation ( Pan et al, 2019 ; Xu et al, 2020 ); however, our study showed that the total dosage of Gns used in our study was not statistically different among the treatment groups, which means a full dose of gonadotropins or prolonged pituitary downregulation would not drastically increase the economic burden for Infertile couples.…”
Section: Discussioncontrasting
confidence: 74%
“…The findings of this study have several strengths. First, the cost of a successful cycle in the GnRH antagonist protocol is high, ranging from ¥6,757.39 to ¥153,327.20 ( Pan et al, 2019 ). Although the GnRH antagonist protocol is better than other protocols in terms of psychosocial and physical well-being during the first ART treatment ( Toftager et al, 2018 ), these data, considering the significant financial investment, may influence physician recommendation or patients’ decision-making regarding a COH protocol and a fresh embryo transfer vs. FET a priori for convenience.…”
Section: Discussionmentioning
confidence: 99%
“…This has an unfortunate consequence, given the fact that the main costs of an IVF cycle occur once the ova are collected. If the IVF cycle results in poor-quality ova, there is no possibility of stopping the procedure in time to restart the cycle to achieve a better stimulation [19]. Hassan et al described the follicular sensitivity index (FSI).…”
Section: Discussionmentioning
confidence: 99%